Assessment of Parental Lines and F1 Hybrid for Earliness and Growth in Cucumber (Cucumis sativus L.) - Hradesh Shivhare,; C.N. Ram,; Aastik Jha,; Anil Kumar,; A.K. Singh,; D. K. Upadhyay,; Santosh Kumar,; Lokesh Yadav,; Virendra Kumar,; Shyam Prakash, (The Bioscan, 2025)
The present investigation was conducted during Zaid season in year 2023-24 (Y1) and 2024-25 (Y2) to evaluate mean performance using Line x Tester mating design with thirteen diverse parents of cucumber. They were crossed in a Line x Tester mating design for generating experimental material. All thirteen parents and their thirty hybrids were grown in randomized block design with three replications. Observations were recorded for the seven traits. The evaluation of parents and hybrids for seven traits over two years and pooled data revealed significant variations. Based on the per se performance findings of the experiment conducted it may be suggested that crosses NDCU-23-3 × Arka Veera, NDCU-23-8 × Pusa Uday, VRCU- 2203× Arka Veera, NDCU-23-5 × Punjab Naveen are the top most hybrids in order of merit for Growth and Earliness. It is suggested to test the superior hybrids in multilocation trial to confirm their potentiality and stability over different agro climatic conditions. Selected parents with desirable per se and combining ability effect can be used in multiple crossing schemes to recombine different productive components.